Analisis Tipe Longsoran Daerah Pohe Kota Gorontalo Berdasarkan Orientasi Struktur Geologi - Usman, Fatma T.; Arifin, Yayu Indriati; Hutagalung, Ronal; Permana, Aang Panji (Universitas Negeri Gorontalo, 2022)
Administratively, the research area is located in Pohe Village, Hulonthalangi sub-district, Gorontalo City, Gorontalo Province. Astronomically, the research area is at coordinates 00030'16.10